Agriculture Production Pattern and Economic Impact of the Magar Community: A Study of Kalika Municipality Chitwan - Dhakal, Chandra Prasad (Nepal Journal of Multidisciplinary Research, 2023)
The Magar is one of the indigenous nationalities of Nepal having with special practice and pattern of agriculture-based economy. The study analyzes agriculture production pattern and economic impact of the Magar living in Kalika municipality Chitwan. The main objective of the study is to analyze how agricultural practice and pattern supports in the livelihood strategy the major. It follows more qualitative and quantitative research design and used both primary and secondary source of data. Findings and conclusion of the study is based on primary data collected from the field study. Primary data were collected through individual interviews and observation. In the course of field visit 50 farmers were randomly selected as respondents. It is found that traditional agriculture based economic pattern of the Magar of study area is changing due to the shifting pattern of livelihood.